Analysis of a mechanical vapor compression desalination system - Aybar, HS (Elsevier Science Bv, 2002)
The mechanical vapor compression (MVC) desalination system is based on distillation of seawater. The system is basically a heat exchanger that is an evaporator/condenser. The heat required to evaporate water which flows on one side of a heat transfer surface is supplied through the simultaneous condensation of the distillate-producing vapor on the other side of the surface. That is, the latent heat is exchanged in the evaporation-condensation process within the system. A compressor is the driving force for this heat transfer and provides the energy required separating the solution and overcoming dynamic pressure losses and other irreversibilities. In this study, the operation characteristics of a low-temperature MVC desalination system are investigated. In the modeling, the overall energy balance and mass balance equations and LMTD method for heat transfer are used. The tube diameter and the tube length were taken at 0.025 m and 9 in, respectively. The main dependent parameters, the compressor work and the mass flow rate of the distilled water, were investigated against the independent parameters, the evaporation side pressure, the condensation side pressure, and the water inlet temperature.
Keywords: desalination; mechanical vapor compression